GEREJA KALIMANTAN EVANGELIS HOSIANA BANJARMASIN - Hendi Kristian; Pakhri Anhar (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The Gereja Kalimantan Evangelis Banjarmasin is a Christian place of worship located in the city of Banjarmasin, South Kalimantan. Starting from the Gospel Preaching in the 19th century, the entry of Protestant Christian teachings in the land of Borneo by missionaries from Germany. Initially known as the Gereja Dayak Evangelis but there was a change to G.K.E, along with the development of the Gereja Kalimantan Evangelis, the increase in the number of congregations and the spiritual needs of Christians also needed to be increased. The church is not only a place of worship, but also a place to shape one's personality, and have a social role in society. The problem is how to facilitate spiritual and social activities for Christians by presenting a religious experience that reminds visitors of the greatness of God. In the problem of the church G.K.E hosiana used the semiotic method namely the icon and symbol approach to answer the problem. The icon and symbol approach is applied to the shape, scale, lighting, material, and texture which can affect the 3 senses of humans, namely hearing and touch, which will give certain reactions to the thoughts and feelings of visitors.